Efficacy and safety of venetoclax plus hypomethylating agents in relapsed/refractory acute myeloid leukemia: a multicenter real-life experience - Angotzi, Francesco; Lessi, Federica; Leoncin, Matteo; Filì, Carla; Endri, Mauro; Lico, Albana; Visentin, Andrea; Pravato, Stefano; Candoni, Anna; Trentin, Livio; Gurrieri, Carmela (Frontiers in Oncology, 2024)
Venetoclax (VEN) has been shown to play a synergistic effect in combination with hypomethylating agents (HMAs) in the frontline treatment of acute myeloid leukemia (AML). However, the potential role of this therapy in the relapsed/refractory (R/R) AML setting, still needs to be further unveiled. The aim of the current study was to retrospectively outline the safety profile, response and survival outcomes of R/R AML patients treated with VEN in association with HMAs. Clinical, biological, and molecular data were collected from 57 patients with R/R AML treated with VEN combined with azacitidine or decitabine between 2018 and 2023. The median age of patients was 63 years, 38 (66.7%) received treatment for relapsed disease while 19 (33.3%) for refractory disease, 5 (8.7%) were treated for molecular relapse. A consistent proportion of the cohort was represented by patients with unfavorable prognostic factors such as complex karyotype (36.8%), secondary AML (29.8%), previous exposure to HMAs (38.6%), and relapse after allogeneic stem cell transplant (22.8%). A total of 14 patients achieved CR (24.6%), 3 (5.3%) CRi, 3 (5.3%) MLFS, and 3 (5.3%) PR, accounting for an ORR of 40.4%. The CR/CRi rate was higher in the group treated with azacitidine than in the group treated with decitabine (37.8% vs. 15%). The median OS was 8.2 months, reaching 20.1 months among responding patients. VEN-HMAs treatment allowed to bridge to allogeneic stem cell transplantation 11 (23.9%) of eligible patients, for which a median OS of 19.8 months was shown. On multivariate analysis, ECOG performance status ≥2, complex karyotype and not proceeding to allogeneic stem cell transplantation after therapy with VEN-HMAs were the factors independently associated with shorter OS. Patients treated with the azacitidine rather than the decitabine containing regimen generally displayed a trend toward superior outcomes. The major toxicities were prolonged neutropenia and infections. In conclusion, this study showed how VEN-HMAs could represent an effective salvage therapy in patients with R/R AML, even among some of those patients harboring dismal prognostic features, with a good toxicity profile. Further prospective studies are thus warranted.